Peran Kepercayaan Sebagai Mediasi Pengaruh E-WOM Negatif Terhadap Niat Beli Pada E-commerce JD.id - APSARI, VERANI (Jurnal Ilmu Manajemen (JIM), 2019)
The research aims to determine and explain the effect of negative e-WOM on purchase intentions through trust as a mediating variable on JD.id e-commerce. This type of research is causal research using a quantitative approach. Data collection techniques using snowball sampling. The number of samples used in the study is as many as 200 respondents who have seen comments on JD.id Instagram but have never made a product purchase on JD.id. The analysis technique used is path analysis with the AMOS program. The results showed that e-WOM negative had a significant effect on trust. Trust had a significant effect on purchase intentions. Negative e-WOM affected purchase intention. Keywords: negative e-WOM; purchase intention; trust.